Uma abordagem geográfica do ensino superior e tecnológico nas cidades pequenas de Areia, Bananeiras e Guarabira – PB - Pereira, Ana Lucia do Nascimento (2020)
This thesis presents a study about higher and technological education in the small cities of Areia, Bananeiras and Guarabira - PB, in view of the use of the time frame that begins in 2003 and ends in 2015, aiming in general to understand the results obtained with the implementation of public policies in the Federal Government aimed at higher and technological education in the cities targeted by this research. We consider the following specific objectives to delineate in an illuminating way: the description of the term small cities, so that we have the real meaning and appropriate value to the cities involved in the research; then a summary was made of the reformulations that have taken place in recent years in the federal government's public policy for higher and technological education at national and local level; and finally, we explain how the process of expansion of higher and technological education in the cities under study occurred during the proposed period. Regarding the methodological paths used for the development and completion of this research, letters were initially sent to the competent bodies in order to obtain answers that would refute the hypothesis that guided the thesis: Due to the investments made by the federal government in higher and technological education in the small cities under study, it was possible to verify an existing centrality among them as a result also of education, in view of the city of Guarabira showing prominence regarding a greater number of students who move and seek to qualify through undergraduate studies, superior or technological. Still in relation to the methodological path, 60 interview scripts (semi-structured) were applied, distributed in 20 for each city surveyed, and later after receiving only some data, these were tabulated and analyzed together with the material collected in the field ( interview script), shown as a form of graphics and defendants with the following purpose: due to the greater advance in the number of students enrolled in the educational institutions analyzed, it was possible to verify that the campuses did receive investments to accommodate the expected demand. However, it is observed that for the time of implementing programs, creating courses and building a campus, the resources have already been supplied. However, over the years and the lack of investment through cuts in education in the country, especially higher education, students, employees, teachers and institutions in general started to suffer from the lack of incentive and improvement in the quality of the work. public education.